Successful venoarterial extracorporeal membrane oxygenation for postoperative septic shock in a child with liver transplantation: A case report. (12th September 2017) - Abe, Michiko; Ide, Kentaro; Nishimura, Nao; Nakagawa, Satoshi; Fukuda, Akinari; Sakamoto, Seisuke; Kasahara, Mureo
Abstract: Refractory septic shock after LT is a life‐threatening complication. VA ECMO is used to treat refractory cardiorespiratory failure. We present herein the case of a 5‐year‐old girl with post‐Kasai biliary atresia, who underwent a living donor LT and suffered refractory septic shock. VA ECMO was indicated due to progressive cardiac deterioration. After full recovery of her EF, she has been steadily improving and has shown good liver function and no neurological sequelae. This is the first report of successful VA ECMO in a post‐ LT patient with refractory septic shock.